Energy, Exergy, and Drying Kinetics Assessment of a Solar-Assisted Heat Pump Dryer for Sustainable Agricultural Product Processing - Qudratullah, Fahmi; Efendi, Irwan Saputra; Hakim, Moh Azizi; Heriyana, Erik; Sukmara, Sony (Integrated Mechanical Engineering Journal, 2024)
Drying is an important agricultural post-harvest operation which requires high energy input and produces inconsistent agricultural products quality by conventional methods. Alternatively, solar assisted heat pump drying can be provided which is more efficient by utilizing both renewable solar heat and heat pump dehumidification and heat recovery. In this study, an integrated drying kinetics, energy analysis and exergy evaluation framework are developed to evaluate the performance of solar-assisted heat pump dryer. The framework describes mathematically derived indicators to describe moisture reduction behavior, drying rate, energy consumption, coefficient of performance, specific moisture extraction rate, drying efficiency, and exergy efficiency. Illustrative results demonstrate that the system continuously reduces the moisture content while increasing the energy utilization in comparison to conventional hot-air drying, where the COP and the SMER are important transients measuring energy delivery for useful purposes and the ability to remove moisture, respectively. Exergy analysis also pinpoints the main exergy-irreversibility sources in the drying chamber and heat-transfer components. The study is overall an integrated mechanical-engineering approach that connects drying behavior, heat transfer, energy consumption and exergy losses for designing and optimizing sustainable and energy efficient dryers for agricultural and food processing applications.